2010
DOI: 10.1038/nature08919
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear atom interferometer surpasses classical precision limit

Abstract: Interference is fundamental to wave dynamics and quantum mechanics. The quantum wave properties of particles are exploited in metrology using atom interferometers, allowing for high-precision inertia measurements. Furthermore, the state-of-the-art time standard is based on an interferometric technique known as Ramsey spectroscopy. However, the precision of an interferometer is limited by classical statistics owing to the finite number of atoms used to deduce the quantity of interest. Here we show experimentall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
1,284
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 887 publications
(1,312 citation statements)
references
References 32 publications
15
1,284
0
Order By: Relevance
“…The largest entanglement depth verified previously has been 170 out of 2300 atoms for a spin-squeezed state [6], and very recently 13 out of 41 atoms for a non-Gaussian state [13].…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…The largest entanglement depth verified previously has been 170 out of 2300 atoms for a spin-squeezed state [6], and very recently 13 out of 41 atoms for a non-Gaussian state [13].…”
mentioning
confidence: 79%
“…This parameter quantifies how widely shared among the particles an entangled state is. For a state of an ensemble characterized by collective measurements, the entanglement depth depends sensitively on the proximity of the state to the ideal symmetric subspace of all particles.The largest entanglement depth verified previously has been 170 out of 2300 atoms for a spin-squeezed state [6], and very recently 13 out of 41 atoms for a non-Gaussian state [13].Here we generate entanglement in a large atomic ensemble by detecting a single photon that has interacted with the ensemble [20]. An incident vertically polarized photon experiences a weak random polarization rotation associated with the quantum noise of the collective atomic spin.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Equation (1) shows that a quantum state with the APEP-enhancing must be entangled. Besides entangled states, it has been theoretically and experimentally demonstrated that spin squeezed states (SSSs) can also be used to improve the accuracy of estimation [8,9,10,11,12,13,14,15,16,17,18,19]. The concept of SSSs was first established by Kitagawa and Ueda [9].…”
Section: Introductionmentioning
confidence: 99%